Toxicity of CuO, ZnO, TiO2 and MWCNT Nanoparticles on Human Pathogenic Bacteria - Kavitha, V.; Ragavendran, V.; Suresh, P.; Shanmughaiah, V.; Mayandi, J.; Mahalingam, P.; Sethupathi, N. (My University, 2019)
Toxicities of CuO, ZnO, TiO2 and MWCNT nanoparticles towards human pathogenic bacteria Bacillus cereus (Gram - negative) and Salmonella typhi (Gram - positive) were determined using serial dilution method on Luria Bertani (LB) agar plate method. The structural and morphological properties of the nanoparticles were characterized using XRD, SEM, EDAX and TEM analysis. The above said human pathogens were inoculated in 20 ml of sterile nutrient broth and it was incubated at 37°C for 12 h. After incubation, the bacterial cultures were treated with nanoparticles (100 μg/ml) and the culture was incubated for 6 hrs. After incubation, 100 μl of culture test tubes was diluted (101 to 107 numbers of colonies) and each dilution were taken on LB agar plates using with spreader. The plates were incubated for 24 hours at 37°C. After incubation, the results were observed plates and colonies were counted. S.typhi: MTCC733 showed the uncountable colonies for all the nanoparticles. However, a countable bacterial colony for each dilution was observed for Bacillus cereus, when treated with ZnO nanoparticles. The CuO demonstrate countable colonies for 103 - 107 dilution, while TiO2 & MWCNT demonstrate countable colonies for 105 - 107 dilution plates.
Keywords: Toxicity; nanoparticles; pathogenic bacteria and antibacterial activity